Myocarditis and coronary aneurysms in a child with acute respiratory syndrome coronavirus 2. (17th December 2020) - Ciuca, Cristina; Fabi, Marianna; Di Luca, Daniela; Niro, Fabio; Ghizzi, Chiara; Donti, Andrea; Balducci, Anna; Rocca, Alessandro; Zarbo, Chiara; Gargiulo, Gaetano Domenico; Lanari, Marcello
Abstract: A 6‐year‐old African boy with multi‐viral infection including parvovirus B19 and severe acute respiratory syndrome coronavirus 2 was admitted for persistent fever associated with respiratory distress and myocarditis complicated by cardiogenic shock needing ventilatory and inotropic support. Coronary aneurysms were also documented in the acute phase. Blood tests were suggestive of macrophage activation syndrome. He was treated with intravenous immunoglobulins, aspirin, diuretics, dexamethasone, hydroxychloroquine, and prophylactic low molecular weight heparin. Normalization of cardiac performance and coronary diameters was noticed within the first days. Cardiac magnetic resonance imaging, performed 20 days after the hospitalization, evidenced mild myocardial interstitial oedema with no focal necrosis, suggesting a mechanism of cardiac stunning related to cytokines storm rather than direct viral injury of cardiomyocytes.